Sucrose feeding during pregnancy and lactation elicits distinct metabolic response in offspring of an inbred genetic model of metabolic syndrome - Sedová, Lucie; Seda, Ondrej; Kazdová, Ludmila; Chylíková, Blanka; Hamet, Pavel; Tremblay, Johanne; Kren, Vladimír; Krenová, Drahomíra (American journal of physiology. Endocrinology and metabolism, 2007)
The importance of early environment, including maternal diet during pregnancy, is suspected to play a major role in pathogenesis of metabolic syndrome and related conditions. One of the proposed mechanisms is a mismatch between the prenatal and postnatal environments, leading to misprogramming of the metabolic and signaling pathways of the developing fetus. We assessed whether the exposure to high-sucrose diet (HSD) alleviates the detrimental effects of sucrose feeding in later life (predictive adaptive hypothesis) in a highly inbred model of metabolic syndrome, the PD/Cub rat. Rat dams were continuously fed either standard or HSD (70% calories as sucrose) starting 1 wk before breeding, throughout pregnancy, at birth, and until weaning of the offspring. After weaning, all male offspring were fed HSD until the age of 20 wk, when detailed metabolic and morphometric profiles were ascertained. The early life exposure to a sucrose-rich diet resulted in distinct responses to longtime postnatal HSD feeding. Offspring of the sucrose-fed mothers displayed higher adiposity and substantial increases in triglyceride liver content together with unfavorable distribution of cholesterol into lipoprotein subfractions. On the other hand, their adiponectin concentrations were significantly higher, and insulin sensitivity of skeletal muscle was enhanced compared with the offspring of standard diet-fed mothers. Triglycerides, free fatty acids, overall glucose tolerance, and the insulin sensitivity of adipose tissue were comparable in both groups. In the genetically identical animals, maternal HSD feeding elicited a variety of subtle effects but did not lead to predictive adaptive protection from most HSD-induced metabolic derangements.
Keywords: Animals; kosterní svaly; novorozená zvířata; cholesterol; glukózový toleranční test; Female; inbrední kmeny potkanů; ženské pohlaví; Sucrose; triglyceridy; laktace; Metabolic Syndrome; Animals, Newborn; Fatty Acids, Nonesterified; Triglycerides; Blood Glucose; Glucose Tolerance Test; Intra-Abdominal Fat; těhotenství; Rats, Inbred Strains; Insulin; metabolický syndrom; Muscle, Skeletal; Cholesterol; Male; kyseliny mastné neesterifikované; Insulin Resistance; nitrobřišní tuk; inzulinová rezistence; krysa rodu Rattus; zvířata; mužské pohlaví; Pregnancy; Lactation; inzulin; krevní glukóza; sacharosa; Rats